Law in crisis the ecstatic subject of natural disaster - Miller, Ruth Austin, 1975- (Stanford, Calif. : Stanford Law, 2009)
Taking natural disaster as the political and legal norm is uncommon. Taking a person who has become unstable and irrational during a disaster as the starting point for legal analysis is equally uncommon. Nonetheless, this book makes the unsettling case that the law demands an ecstatic subject and that natural disaster is the endpoint to law. Developing an idiosyncratic but compelling new theory of legal and political existence, the book challenges existing arguments that, whether valedictory or critical, have posited the rational, bounded self as the normative subject of law.
Specialized.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Law -- Philosophy; Subjectivity; Natural disasters -- Law and legislation; Law -- Political aspects; Law; Interdisciplinary studies; Jurisprudence & general issues; Law & society, sociology of law; Natural disasters